The Effects of the Toxic Cyanobacterium Limnothrix (Strain AC0243) on Bufo marinus Larvae - Olivia Daniels; Larelle Fabbro; Sandrine Makiela (Toxins, 2014)
Limnothrix (strain AC0243) is a cyanobacterium, which has only recently been identified as toxin producing. Under laboratory conditions, Bufo marinus larvae were exposed to 100,000 cells mL−1 of Limnothrix (strain AC0243) live cultures for seven days. Histological examinations were conducted post mortem and revealed damage to the notochord, eyes, brain, liver, kidney, pancreas, gastrointestinal tract, and heart. The histopathological results highlight the toxicological impact of this strain, particularly during developmental stages. Toxicological similarities to β-N-Methylamino-L-alanine are discussed.